Effects of temporal muscle detachment and coronoidotomy on facial growth in young rats - Fernanda Engelberg Fernandes Gomes; Rogério Bonfante Moraes; João Gualberto de Cerqueira Luz (Sociedade Brasileira de Pesquisa Odontológica, 2012)
This study analyzed the effects of unilateral detachment of the temporal muscle and coronoidotomy on facial growth in young rats. Thirty one-month-old Wistar rats were distributed into three groups: detachment, coronoidotomy and sham-operated. Under general anesthesia, unilateral detachment of the temporal muscle was performed for the detachment group, unilateral coronoidotomy was performed for the coronoidotomy group, and only surgical access was performed for the sham-operated group. The animals were sacrificed at three months of age. Their soft tissues were removed, and the mandible was disarticulated. Radiographic projections-axial views of the skulls and lateral views of hemimandibles-were taken. Cephalometric evaluations were performed, and the values obtained were submitted to statistical analyses. There was a significant homolateral difference in the length of the premaxilla, height of the mandibular ramus and body, and the length of the mandible in all three groups. However, comparisons among the groups revealed no significant differences between the detachment and coronoidotomy groups for most measurements. It was concluded that both experimental detachment of the temporal muscle and coronoidotomy during the growth period in rats induced asymmetry of the mandible and affected the premaxilla.